Wall shear stress prediction using computational simulation on patient specific artery with aneurysm - Yunus, M. (EDP Sciences, 2014)
An aneurysm is formed when a blood vessel becomes dilated or distorted. It will cause the vessel to expand to a size greater than its original diameter. In this study, Wall Shear Stress (WSS) of cerebral artery with aneurysm was predicted using Computational Fluid Dynamics (CFD). WSS in the artery is one of the indicators for brain artery disease progression. Based on the results, the maximum value of blood velocity and WSS on patient specific artery with aneurysm are 3.23 m/s and 60.1 Pa, respectively. The location of high WSS is before and after the aneurysm bulge. The WSS is above the normal physiological value where the artery wall is exposed to high stress. Hence, the vessel at this location is anticipated to become weaker and could be further dilated. Â© 2014 Owned by the authors, published by EDP Sciences.